Music therapy in psychological and educational context: Enhancing emotional and cognitive development of students - YingDong Guo (Acta Psychologica)
In recent years, music therapy has gained popularity, sparking interest in examining its effectiveness. The primary objective of this article is to analyze the effectiveness of an intervention program of music therapy on the emotional and cognitive development of young individuals. The study design is the intervention-control study. The participants consisted of 140 students from a university in Ukraine: 70 individuals diagnosed with clinical depression and 70 individuals who did not report any psychological disorders. The instruments utilized included the Psychological General Well-Being Index, Wechsler Memory Scale, and Conners' Continuous Performance Test-Second Edition. The results indicated that music therapy led to a significant improvement in the measured parameters across both contexts, albeit with varying degrees of effectiveness. In the educational context, psychological well-being increased by 10.40 points (p = 0.000), memory by 1.89 points (p = 0.005), and attention by 1.69 points (p = 0.000). In the psychological context, the effects were more pronounced: psychological well-being increased by 11.92 points, memory by 3.31 points, and attention by 1.57 points (all p = 0.000). Furthermore, effect size analysis revealed that music therapy exerted a very large impact in the psychological context on psychological well-being (d = 3.71), memory (d = 2.67), and attention (d = 1.17), whereas in the educational context, the effects were significant but comparatively lower (d = 4.36, 0.90, and 0.67, respectively). These findings highlight the differential impact of music therapy depending on the context of its implementation, emphasizing the necessity of context-specific approaches to maximize its benefits. This study contributes to the growing body of research demonstrating the effectiveness of music therapy in both psychological treatment and educational enhancement, supporting its broader integration into mental health and academic settings.